Unique Epigenetic Programming Distinguishes Regenerative Spermatogonial Stem Cells in the Developing Mouse Testis - Keren Cheng; I-Chung Chen; Ching-Hsun Eric Cheng; Kazadi Mutoji; Benjamin J. Hale; Brian P. Hermann; Christopher B. Geyer; Jon M. Oatley; John R. McCarrey (iScience, 2020)
Summary: Spermatogonial stem cells (SSCs) both self-renew and give rise to progenitors that initiate spermatogenic differentiation in the mammalian testis. Questions remain regarding the extent to which the SSC and progenitor states are functionally distinct. Here we provide the first multiparametric integrative analysis of mammalian germ cell epigenomes comparable with that done for >100 somatic cell types by the ENCODE Project. Differentially expressed genes distinguishing SSC- and progenitor-enriched spermatogonia showed distinct histone modification patterns, particularly for H3K27ac and H3K27me3. Motif analysis predicted transcription factors that may regulate spermatogonial subtype-specific fate, and immunohistochemistry and gene-specific chromatin immunoprecipitation analyses confirmed subtype-specific differences in target gene binding of a subset of these factors. Taken together, these results show that SSCs and progenitors display distinct epigenetic profiling consistent with these spermatogonial subtypes being differentially programmed to either self-renew and maintain regenerative capacity as SSCs or lose regenerative capacity and initiate lineage commitment as progenitors.